Efecto de dos tipos de aceite esencial (naranja y romero) en la conservación de pescado fresco cachema corvina (cynoscion spp) y su influencia en las propiedades físicas y microbiológicas. - Molina Paredes, Patricio Fernando (2018)
Fish are considered as very perishable foods, their physical, chemical and microbiological compositions are altered quickly and easily. Unless appropriate conservation methods are used, the objective of this research was to evaluate the effect of two types of essential oil (orange and Rosemary) in the conservation of fresh fish cachema corvina (Cynoscion spp) and its influence on the physical properties and microbiological. The immersion of essential oils was carried out for 10 minutes in the fillets of properly washed fish which we went to 9 treatments with 3 repetitions. At the same time, physicochemical analyzes were carried out, such as: pH, protein, total fat, humidity and microbiological analysis: total aerobic counts, escherichia coli to determine if there is a difference between the levels of the treatments studied. In the statistical analysis, a factorial arrangement of AxB with 3 replications was used in a controlled environment considering as factor A: orange essential oil, factor B: Rosemary essential oil. The statistical package SPSS was used to analyze the data, and the Tuckey significance test was used to separate the mean levels of the treatments (p<0.05). At the end of the investigation it was concluded that there is a significant difference between the levels of the treatments. Therefore, the best treatment is chosen: A0B2 (0%of essential oil of orange and 0.6%of essential oil of Rosemary); since it was determined that I do not present any content value of microorganisms.